Pengaruh Overconfidence, Toleransi Risiko, dan Perilaku Keuangan Terhadap Keputusan Berinvestasi di Bursa Efek Indonesia - Syahfitri, Diah Intan; Tryana, Ayu Levia (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to analyze the effect of overconfidence, risk tolerance, and financial behavior on investment decisions on the Indonesia Stock Exchange. Using the Structural Equation Modeling (SEM) approach with Partial Least Squares (PLS), this study involved respondents who are millennials and active investors in the Indonesian capital market and live in Sumbawa Regency with a total of 100 respondents. Data was collected through a questionnaire designed to measure the level of overconfidence, risk tolerance, and financial behavior, as well as investment decisions made by respondents. The results of the analysis show that overconfidence has a positive and significant influence on investment decisions, where more confident investors tend to make more aggressive investment decisions. In addition, risk tolerance is also shown to contribute positively in influencing investment decisions, with investors who have high risk tolerance being more willing to invest in riskier instruments. Financial behavior, as a factor that influences the decision-making process, shows a significant relationship to investment decisions. These findings provide insights for investors and financial practitioners in understanding the psychological factors that influence investment decisions in the capital market, as well as the importance of behavior management in improving investment returns.